ANALISA PENERAPAN KNOWLEDGE MANAGEMENT PADA PERUSAHAAN SERVICE (STUDI KASUS PT. PIT ELEKTRONIK - Wahyudi Wahyudi (LPPM Nusa Mandiri, 2018)
Knowledge management is an emerging concept in the field of management and widely adopted within the organization to improve organizational performance. This study discusses the PT PitElektronik readiness in implementing knowledge management. Questionnaires were distributed to the technicians, service head section, and manager of PT PitElektronik. Data were collected using a structured questionnaire and analyzed using descriptive statistical techniques and prototype. From the calculation results show that knowledge management as a whole has achieved optimal conditions, which indicates that the organization is ready to implement knowledge management. This study recommends that the initiative must be taken by the organization to adopt KM practices to gain more competitive advantage.